2020
DOI: 10.1101/2020.06.24.20138891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitude, Perceptions and Practice towards COVID-19: A systematic review and Meta-analysis

Abstract: Background: Several studies among various population groups have been conducted to investigate the level of knowledge, attitudes, perceptions, and risk reduction practices (KAP) related to COVID-19. A comprehensive review on this topic is important to highlight the areas for improvement and interventions to prevent COVID-19. Thus, the purpose of this study was to summarize the level of KAP about COVID-19 via a systematic review Methods: A systematic literature search was performed using a combination of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 44 publications
9
32
2
Order By: Relevance
“…The study showed a generally good knowledge amongst HCWs varying from about 50–90% with a pooled average of nearly 80%. This finding is consistent with a previous study done by Akshaya and his colleagues [ 30 ]. The subgroup analysis showed that HCWs from the Amhara region were more knowledgeable compared with those from the Ethiopian capital, Addis Ababa and were more knowledgeable in June compared with March.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The study showed a generally good knowledge amongst HCWs varying from about 50–90% with a pooled average of nearly 80%. This finding is consistent with a previous study done by Akshaya and his colleagues [ 30 ]. The subgroup analysis showed that HCWs from the Amhara region were more knowledgeable compared with those from the Ethiopian capital, Addis Ababa and were more knowledgeable in June compared with March.…”
Section: Discussionsupporting
confidence: 94%
“…The pooled level of poor practice for protective measures against COVID-19 was low at 40%. This was relatively lower than that found in a previous study Bhagavathula and his colleagues [ 30 ]. The reasons for this are unclear but may have to do with protective mechanisms conflicting with normal lifestyles, especially amongst the poorer sectors of the population.…”
Section: Discussioncontrasting
confidence: 69%
“…In this study, the pooled proportion of participants with a good attitude regarding COVID-19 was 69.08% (95% CI: 55.42, 81.24), which was low for controlling viral transmission. This result is consistent with the findings reported by Bekele et al, in which 70–97.1% had a good attitude, 31 and higher than the 46% (95% CI: 15, 77) reported by Bhagavathula et al 32 The pooled proportion of positive attitudes regarding COVID-19 was low compared to that for knowledge in this study. The highest and lowest proportions of positive attitudes were observed in Addis Ababa (89.80%) and the Amhara (61.50%) region, respectively, in the subgroup analysis.…”
Section: Discussionsupporting
confidence: 93%
“…78.02). This proportion is consistent with that reported by Bekele et al, in which 40–99.5% of participants had good knowledge of COVD-19 31 and higher than the 56.6% (95%CI: 45%) reported by Bhagavathula et al 32 The knowledge of people regarding COVID-19 in the present study was low at the country level. The subgroup analysis indicated a higher knowledge in institution-based studies (73.91%) compared to community-based studies (62.60%).…”
Section: Discussionsupporting
confidence: 92%
“…This finding was very different from a systematic review and meta-analysis result of 73%. 39 The possible justifications might be study area and sample size (27,617) differences.…”
Section: Discussionmentioning
confidence: 99%